The Effect of Rewards and Punishment on Student Learning Motivation on Stoichiometry Material - Rosanna, Desi Lisa; Hajijah, Aida (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research is motivated by students' learning motivation which is still in the low category. Giving reward and punishment to students aims to motivate students so that they learn better. This study aims to determine whether there is an effect of reward and punishment on students' learning motivation in stoichiometry material. The subjects of this study were 10th grade students at public high school at Pekanbaru City, Indonesia. This study using a purposive sampling technique with consideration of classes having low learning motivation and obtained first class as an experimental class and second class as a control. Data collection techniques used are questionnaires, observation, and documentation. Final data analysis in this study using the t test. From the results obtained, the value of t-count = -3.720 and t-table = 2.04 at a significant level of 5% and Sig. (2-tailed) of 0.001. From this study it was concluded that t-count t-table and Sig. (2–tailed) 0.05. So the null hypothesis (H0) is rejected and Ha is accepted. This means that there is a significant effect of reward and punishment on student motivation in stoichiometric material with an effect coefficient of 10.12%.